A Young Male with Progressive Pallor (Journal of Medicine, 2011)
Dyserythropoiesis occurs in a variety of congenital and acquired haematological disorders. The term congenital dyserythropoictic anaemia was first used by Crookston et al. CDA comprises a group of rare hereditary disorders of erythropoiesis which are characterized by distinct morphological abnormalities of erythroblasts in the bone morrow. CDA is classified into three classical types (type I, II and III).Most cases of CDA are diagnosed early in life. Our patient was diagnosed at the age of 22 years with clinical presentation of anaemia, hepatomegaly and bone marrow morphology compatible with CDA type III. We report this case for rarity. Keyword: Dyserythropoiesis, Congenital Dyserythropoictic Anaemia (CDA), Bone morrow DOI: http://dx.doi.org/10.3329/jom.v12i2.8427 JOM 2011; 12(2): 183-184